Burkina Faso : Poverty Reduction Strategy Paper; Annual Progress Report Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report ;, 2008)
This annual progress report reviews the joint staff advisory note on Burkina Faso's Poverty Reduction Strategy Papers (PRSPs). IMF staff highlights the importance of increasing public revenue mobilization and strengthening expenditure management and efficiency, and securing financing in the form of grants, which would create space for an increase in pro-poor spending. Increasing spending on basic services and enhancing the management and efficiency of public expenditure in health and education, and continued progress on decentralization are critical to achieve the PRS public service delivery targets.